PENERAPAN SCAFFOLDED DEBATE BATTLE CARD UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI PESERTA DIDIK KELAS VIIE SMP LABORATORIUM UM - Fatikasari, Achsania Devi; Rahayu, Linda Zulkifa; Kurniawan, Bayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low verbal communication skills have become a significant challenge in 21st century learning, especially at the junior high school level. Based on the results of the initial questionnaire in class VIIE SMP Laboratorium UM, most students have difficulty expressing their opinions orally, and many feel limited in vocabulary mastery, which has an impact on low discussion participation and argumentation skills. This study aims to develop and test the effectiveness of Scaffolded Debate Battle Card media in improving students' communication skills. Using the Design Thinking approach which consists of five stages (empathize, define, ideate, prototype, and test), researchers developed learning media in the form of six types of structured debate cards (Statement Card, Evidence Card, Counter Argument Card, Rebuttal Card, Logical Fallacy Card, and Wild Card) equipped with Debate Analysis Sheets. The implementation was conducted on the topic “The Influence of Geographical Factors on Cultural Diversity” involving 32 learners who were divided into pro and contra groups. The results showed substantial improvement on various dimensions of oral communication. Learners showed a marked reduction in communication barriers, including less difficulty expressing opinions, less fear of public speaking, increased ability to explain ideas clearly, and better word choice in discussions. Debate preparation skills showed significant improvement, especially in students' ability to gather additional information and develop a deeper understanding of the debate topic. The media proved effective in overcoming psychological and technical barriers in verbal communication, as well as increasing students' confidence and motivation to learn in the context of social studies learning.